Functional behavioral assessment : a three-tiered prevention model - Filter, Kevin J.; Alvarez, Michelle (New York ; Oxford : Oxford University Press, 2011)
In schools, functional behavioural assessment (FBA) is traditionally applied to special education contexts. This book describes how FBA can improve the behaviour of all students using a three-tiered prevention model.
Includes bibliographical references and index.
Also issued in print format.
Description based on print version record.
Keywords: Behavior modification -- Methodology; Behavioral assessment -- Methodology; Problem children -- Education